Definition and measurement of natural dister damage cost by Ramsey growth model - Hisa Morisugi; Masafumi Morisugi (European Regional Science Association (ERSA), 2012)
This study proposes a consistent definition of natural disaster damage costs, i.e., equivalently, of natural disaster prevention benefits in accordance with general definition of benefits, Willingness to Pay, more concretely, Equivalent Variation, of any policy such as tax reforms, transportations, environments, infrastructures, etc. In order to formulate the damage cost it needs to model the economic behavior at and after the disaster periods given the disaster physical damages are measured by the equivalent labor loss and the equivalent capital stock loss. The model is composed of two stages. The first is the static general equilibrium given the labor loss and the equivalent capital stock loss measured above, for which this study will adopt the static computable general equilibrium (SCGE). The second is the dynamic macroeconomics which models the recovery process given the initial labor and capital stock for cases with and without disaster, for which this study will adopt the dynamic computable general equilibrium (DCGE). The damage cost or benefit of the disaster is defined as the present value of the time stream of Equivalent Valuation for the time stream of utility change due to the initial condition change. Then it will be shown that the conventional damage calculation by the reconstruction and/or replacement cost is assumes that the second stage immediately takes place at the disaster time, therefore, the first stage does not happens. Also sometimes the economic impacts on GDP of disaster capital stock loss are calculated but nothing is referred to the damage cost of disaster. This is because there is not yet clear definition of damage cost and lack of recognition of it is a work of only the first stage. Finally it will be discussed how to transform the disaster physical damages to the equivalent labor and capital stock loss. The physical damages are either private capital loss or labor loss or output loss or social overhead capital loss, each of which enters to CGE as private capital loss, labor force loss, efficiency parameter reduction due to both output loss and social overhead capital loss. Then assuming constant returns to scale the efficiency parameter change due to both output loss and social overhead capital loss can be transformed to the loss of labor and capital stock.
Keywords: H43; 330; project evaluation; disaster damage cost; DCGE; cost benefit analysis